PENERAPAN SAPTA PESONA OBJEK WISATA SAKO DI KANAGARIAN SAKO KECAMATAN RANAH AMPEK HULU KABUPATEN PESISIR SELATAN - Susanti, Anita - (Pendidikan Geografi, 2014)
To achieve the purpose of tourism industry of the community have to apply seven charm with a maximum in the attraction. So with the seven charm filter downll Feb filter many tourists visit in the tourist, because nobodys third manager, community workers and no filter in the surrounding attractions have to be apply seven charm with a down, up and domestic tourists macanegara coming to pick objects the tourist. Research for this aims know application of seven charm Attraction In villages Sako District the Ranah Ampek Hulu Pesisir Selatan District. Filter method in use in this research is qualitative. Informant in this study was the guardien of the country, the head of the village, the filter stay around attraction Sako filter and visiton came to the attraction. Results of this study found that: 1) the security Attraction Sako already applied with both the public and officers may filter is in the attraction, so there is no control of the filter should be in front of tourists which visit to tourist Sako. 2) also lacks Order filter is in the tourist Sako, see all this in place of least procurement parking place and no ticket their compilation into tourist Sako. 3) be less clearness filter applied community and get an officer in tourist Sako, waste filter bones and still less his disposal waste filter in provide by firefighters around the attraction. 4) cold Attraction Sako already maximized, because the natural filter also natural. 5) The beauty of this tourist Sako already the maximum, because the tree- like filter are green. 6) Sustainable Tourism in nice Sako already applied with both the public and officers may filter is in the tourist Sako. 7) already applied cry charm with good memories of nobody public and firefighters filter is in the tourist Sako.